1992
DOI: 10.4992/psycholres1954.34.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loss of control over food acquisition on subsequent disk-pull escape learning

Abstract: The present study examined whether or not a loss of control over food acquisition would interfere with disk pulling shock escape learning. The loss-of-control rats, which had experienced loss of control over food delivery, and the lack-of-control rats, which had received noncontingent food delivery without a prior history of control over food, were impaired on acquisition of the fixed ratio (FR) 2 disk-pull escape compared to the response-contingent, the continuous-reinforcement (CRF)-control, and the home-cag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This phenomenon has been termed the learned helplessness effect; it has been hypothesized that learning about noncontingency between response and outcome produces the learning of uncontrollability, and results in deleterious effects (Maier & Seligman, 1976;Seligman, 1975). Some experiments found that the learning of uncontrollability in an appetitive situation interferes with subsequent learning in aversive or appetitive situation (Caspy & Lubow, 1981;Goodkin, 1976;Job, 1987Job, , 1988Job, , 1989Sonoda, Hirai, & Okayasu, 1992;Sonoda, Okayasu, & Hirai, 1991). These findings are formally similar to effects seen in experiments with pretreatment of uncontrollability over shock.…”
mentioning
confidence: 56%
“…This phenomenon has been termed the learned helplessness effect; it has been hypothesized that learning about noncontingency between response and outcome produces the learning of uncontrollability, and results in deleterious effects (Maier & Seligman, 1976;Seligman, 1975). Some experiments found that the learning of uncontrollability in an appetitive situation interferes with subsequent learning in aversive or appetitive situation (Caspy & Lubow, 1981;Goodkin, 1976;Job, 1987Job, , 1988Job, , 1989Sonoda, Hirai, & Okayasu, 1992;Sonoda, Okayasu, & Hirai, 1991). These findings are formally similar to effects seen in experiments with pretreatment of uncontrollability over shock.…”
mentioning
confidence: 56%
“…As in other countries, learned helplessness effect is more popular than the irrelevance effects among Japanese researchers. A series of rat studies have been conducted by psychologists of Sophia University (Okayasu, 1987, 1989; Sonoda, 1990, 1996; Sonoda, Okayasu, & Hirai, 1991; Sonoda & Hirai, 1992, 1993a, 1993b; Sonoda, Hirai, & Okayasu, 1992). They have successfully demonstrated learned helplessness in cross‐outcome transfer designs.…”
Section: Associative Retardation: Learned Irrelevance and Helplessnessmentioning
confidence: 99%